1056. Predicting Central Nervous System Complications in Staphylococcus aureus Bacteremia Using Clinical Scoring System. (26th November 2018) - Kim, Chung-Jong; Song, Kyoung-Ho; Kang, Chang Kyung; Choe, Pyeong Gyun; Bae, Ji Yun; Choi, Hee Jung; Jung, Younghee; Lee, Seung Soon; Park, Wan Beom; Bang, Ji Hwan; Kim, Eu Suk; Park, Sang Won; et al.
Abstract: Background: Central nervous system (CNS) complications occurring in patients with Staphylococcus aureus bacteremia (SAB) are the most severe complications. In this study, we compared clinical data of SAB patients between cases with and without CNS complication and analyzed the risk factor of CNS complications. Methods: Data from cases with SAB occurred during 5 years at four hospitals were collected. The presence of CNS complications was confirmed by brain MRI, CT, or lumbar puncture. We excluded the cases who already had CNS lesions such as trauma, brain tumor, or cerebrovascular accident. We also excluded the cases who were died or transfer out <7 days of bacteremia onset. Cases were divided into complication group or noncomplication group according to the presence of CNS complication. We compared the clinical profiles between the groups, and analyzed the risk factor of CNS complications by multivariate logistic regression analysis. Results: A total of 1, 085 cases of SAB patients were included. Among these, 43 (4%) cases were complication group (embolic infarct [ n = 23], brain hemorrhage [ n = 8], infarct with hemorrhage [ n = 8], and brain abscess or meningitis [ n = 4]), while 810 (74%) cases were noncomplication group. Two hundred and forty-one cases were excluded. The results of multivariate analysis were shown in table. When selecting by having less than three factors among SOFA > 5, methicillin-susceptible, endovascular infection (weight 2), presence of metastatic infection and community onset, it helps to exclude CNS complications (AUC of ROC curve = 0.77, P < 0.01, sensitivity; 67.5%, specificity: 75.5%, positive predictive value: 12.9%, negative predictive value 97.7%). Conclusion: CNS complication could be excluded by using clinical variables Disclosures: All authors: No reported disclosures.